Wolf Hall [videorecording (DVD)] - Rylance, Mark; Lewis, Damian, 1971-; Foy, Claire, 1984-; Hill, Bernard, 1944-; Mantel, Hilary, 1952-; Mantel, Hilary, 1952- (2015)
Thomas Cromwell is a brutal blacksmith's son who rises from the ashes of personal disaster and deftly picks his way through a court where 'man is wolf to man.' King Henry VIII is obsessed with protecting the Tudor dynasty by securing his succession with a male heir to the throne. Told from Cromwell's perspective, "Wolf Hall" follows the complex machinations and back room dealings of this pragmatic and accomplished power broker who must serve king and country while dealing with deadly political intrigue, Henry VIII's tempestuous relationship with Anne Boleyn, and the religious upheavals of the Protestant reformation.